Ending Over‐lending: Assessing Systemic Risk with Debt to Cash Flow1. (4th August 2015) - Ramsay, Bruce A.; Sarlin, Peter
Abstract: This paper introduces the ratio of debt to cash flow (D/CF) of nations and their economic sectors to macroprudential analysis, particularly as an indicator of systemic risk and vulnerabilities. While leverage is oftentimes linked to the vulnerability of a nation, the stock of total debt and the flow of gross savings is a less explored measure. Cash flows certainly have a well‐known connection to corporations' ability to service debt. This paper investigates whether the D/CF provides a means for understanding systemic risks. For a panel of 33 nations, we explore historic D/CF trends and apply the same procedure to economic sectors. In terms of an early‐warning indicator, we show that the D/CF ratio provides a useful additional measure of vulnerability to systemic banking and sovereign crises, relative to more conventional indicators. As a conceptual framework, the assessment of financial stability is arranged for presentation within four vulnerability zones and exemplified with a number of illustrative case studies. Copyright © 2015 John Wiley & Sons, Ltd.